Kepemimpinan Kyai dalam Meningkatkan Kinerja Tenaga Pendidik di Pondok Pesantren - Widyatmoko, Galih (Journal of Educational Research, 2023)
This article discusses the leadership of kyai at the Raudhatul Mujawwidin Islamic boarding school in an effort to improve the performance of teaching staff, and efforts to improve the quality of educational services to the community and the entire academic community at the Raudhatul Mujawwidin Islamic boarding school. The problem studied is why does Kyai's charismatic leadership go hand in hand with improving the performance of teaching staff? This article comes from qualitative research in which data was extracted using observation, interviews and documentation. This research found that the leadership possessed by kyai in improving the performance of teaching staff is a type of leadership that is charismatic, firm and disciplined. The performance that has been carried out by teaching staff is in the form of a process of guidance, direction, action and evaluation. The efforts made by Kyai to improve the performance of teaching staff are by reinforcing the role and managerial functions of the organization. Artikel ini membahas tentang kepemimpinan kyai di pondok pesantren Raudhatul Mujawwidin dalam upaya meningkatkan kinerja tenaga pendidik, dan upaya untuk meningkatkan mutu layanan pendidikan kepada masyarakat dan seluruh civitas akademika di pondok pesantren Raudhatul Mujawwidin. Permasalahan yang dikaji adalah mengapa kepemimpinan karismatik Kyai justru berjalan seiringan dengan peningkatan kinerja tenaga pendidik? Artikel ini berasal dari penelitian kualitatif yang penggalian datanya dilakukan secara observasi, wawancara, dan dokumentasi. Penelitian ini menemukan bahwa kepemimpinan yang dimiliki  kyai dalam meningkatkan kinerja tenaga pendidik adalah tipe kepemimpinan yang kharismatik, tegas dan disiplin. Kinerja yang telah dilaksanakan tenaga pendidik berupa proses bimbingan, pengarahan, tindakan, dan evaluasi. Adapun upaya yang dilakukan oleh Kyai dalam peningkatan kinerja tenaga pendidik adalah dengan memperkuat kembali peran dan fungsi manajerial organisasi.